Hypofractionated concurrent chemoradiotherapy related lymphopenia and its association with survival in locally advanced non-small cell lung cancer patients - Liu, FangJie; Wu, YingJia; Shao, JianHui; Qiu, Bo; Guo, SuPing; Luo, QiaoTing; Guo, JinYu; Wang, DaQuan; Chu, Chu; Zhou, Rui; Chen, NaiBin; Ai, XinLei; et al. (Frontiers in Oncology, 2022)
Background: To evaluate longitudinal changes of concurrent chemoradiotherapy (CCRT) related lymphopenia and its association with survival in locally advanced non-small cell lung cancer (LA-NSCLC) patients. Methods: Total lymphocyte count (TLC) at baseline, weekly intervals during CCRT and monthly intervals up to 12 months after CCRT were documented. The Common Terminology Criteria for Adverse Events version 5.0 was used to grade the severity of lymphopenia. Cox regression analysis was performed to evaluate the association between overall survival (OS) and CCRT related lymphopenia at different timepoints. Logistic regression model was used to determine the clinical factors associated with TLC level. Results: 381 LA-NSCLC patients treated with definitive CCRT without consolidation therapy (NCT02573506/NCT02577341) between 2011 to 2020 were analyzed. With a median follow-up of 45.8 months, the median OS was 41.0 months for all patients. Univariable analysis demonstrated that the 3 weeks during CCRT Grade (G) 4 lymphopenia (P=0.018), 2 months after CCRT G1-4 lymphopenia (P=0.004), 6 months after CCRT (6m-post-CCRT) G1-4 lymphopenia (P=0.001), and TLC nadir (P=0.020) were significantly associated with poorer OS. Multivariable analysis suggested that 6m-post-CCRT G1-4 lymphopenia (HR 2.614; P=0.041) were one of the independent predictors of OS. Further analysis inferred that radiation dose (OR: 1.328; P=0.005), GTV volume (OR: 1.004; P=0.036), and baseline TLC (OR: 0.288; P=0.001) were associated with 6m-post-CCRT lymphopenia. Conclusion: The persistent lymphopenia at 6 months after CCRT was an independent prognostic factor of OS in LA-NSCLC patients. Higher radiation dose, larger gross tumor volume and lower baseline TLC were significantly related to 6m-post-CCRT lymphopenia.